Strategi Bawaslu Dalam Mencegah Pelanggaran Administratif Di Pilkada Kota Medan Tahun 2020 - Rambe, Faisal Hamid; Sintara, Dani; Yeltriana, Yeltriana; Harahap, Syahrul Bakti (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of Bawaslu in preventing administrative violations during the 2020 regional election. For data analysis, this research uses qualitative methods and a normative approach. The research sources are the Chairman of the Medan City Bawaslu and the Violation Resolution Division. Data was collected through literature review, observation, interviews, documentation, and triangulation. Bawaslu is tasked with improving the quality of election implementation to ensure the sovereignty and purity of the people's votes. Bawaslu's scope of duties as the election implementer is very limited. Many news articles mention that the Election Supervisory Board (Bawaslu) does not adequately oversee the election process. The public's expectations of the Election Supervisory Board (Bawaslu) are very high, but its authority is limited. However, on the contrary, Bawaslu does not have sufficient authority to carry out its duties. Bawaslu is tasked with improving the quality of election implementation to ensure the sovereignty and purity of the people's vote results. The scope of Bawaslu's duties as the election organizer is very limited. Many news reports mention that the Election Supervisory Board (Bawaslu) did not adequately oversee the election process. The public's expectations of Bawaslu are very high, but their authority is limited. The implementation of the election will be disrupted if the duties of the Election Supervisory Board (Bawaslu) are not effective. Research results show that Bawaslu has an important role and duties as stipulated in the legislation, including overseeing the stages of the election process and preventing election